Adoption And Utilisation Of Learning /Course Management Systems: The Study Of University Of Professional Studies, Accra - Adjin-Tettey, T.D. (https://www.researchgate.net/publication/265913740, 2014)
Technological changes are having a great impact on teaching and learning all over the world. Students in Ghana at the various levels, especially, the tertiary level are also becoming more technologically inclined with most of them owning computers and having access to the world wide web. Access to smart phones is even making this easier. Oblinger and Oblinger, (2005) describe net generation students as highly literate, preferring to learn by doing experiential and also at ease with image-rich environments than text. For these and many other reasons, many universities (and even some senior secondary schools) around the world have course materials, lectures and discussions online in addition to classroom-based learning. Once online, students can access the latest information at any time and make copies of materials or download course materials and even partake in discussion forums, quizzes and turn in assignments online. Students can also communicate with instructors and other students whenever their schedules permit. This study sought to find out of the level of acceptance of the system and whether it is helping students get more from their courses. It also tested the some of the assumptions of the technology acceptance model (TAM) on which the study was based.
Research Article
Keywords: Adoption; Utilisation; Moodle; Course Management Systems (CMS)